Perubahan Pola Belajar dan Mengajar dengan Alat Bantu Komputer - R. Soegeng (Institut Teknologi Bandung, 2002)
This paper compares the system of learning and teaching forty years ago and at present. At that time in the classroom lecturers used chalk and blackboard, and students went to the library to read some books suggested by their lecturers. At present, some lecturers not only use chalk and blackboard but also computer softwares. These softwares are very helpful for the students because most of them are equiped with visualizations. Therefore, students not only listen to the explanations given by their lecturers, but also see its visualizations. Serious students not only go to the library, but also visit some websites. Many of the articles are equiped with visualizations which can be downloaded.